Prinsip Nielsen pada Redesign User Experience SIMKOPDES - Bintang Danuarta; Oman Komarudin; Aries Suharso (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Sistem Informasi Koperasi Desa Merah Putih (SIMKOPDES) is a digital platform to modernize cooperative governance in rural areas. However its implementation faces challenges due to the digital literacy gap among administrators and an existing interface design that triggers cognitive overload. This study aims to redesign the SIMKOPDES interface using the Design Thinking method. The problem identification stage was conducted comprehensively using Heuristic Evaluation (HE) based on Nielsen 10 Principles by experts and Cognitive Walkthrough (CW) by end users. The redesign solutions focused on simplifying navigation flows, adjusting terminology to match the mental models of rural users, and providing clear visual feedback. Final testing of the new prototype was conducted using the UEQ instrument with 20 rural cooperative administrators as respondents. The measurement results showed a highly significant improvement with all scales achieving positive values. Overall, the evaluation results demonstrate a substantial improvement in user experience, with an average UEQ score increase of 3.04 points from the existing system to the redesigned prototype. The most significant improvement was recorded in the Perspicuity dimension, which increased from -0.89 to 2.05, indicating that the prototype is considerably easier to understand and learn for users. In the benchmark comparison five scales were categorized as Excellent and the Novelty scale as Good. This proves that user experience engineering based on heuristic principles successfully created an adaptive, friendly, and inclusive SIMKOPDES interface for cooperative administrators with limited digital literacy.